Recurrent and Life-Threatening Peripartum Cardiomyopathy: Diagnosis, Delivery Considerations, and Management - Aldrugh, Summer (JACC Case Rep, 2020)
Peripartum cardiomyopathy is an idiopathic reduction in left ventricular systolic function (ejection fraction <45%) toward the end of pregnancy or in the months after delivery. A multidisciplinary approach to management with shock team support is key to identifying and adequately treating patients with refractory heart failure and peripartum cardiomyopathy. (Level of Difficulty: Intermediate.)